Psalm 136: "n Liturgie as herinnering en herbelewenis van God se krag in die skepping en in die geskiedenis - Human, Dirk J. (HTS teologiese studies, 2005)
Psalm 136: A liturgy as remembrance and reenactment of God’s power in creation and historyPsalm 136 is a litany in which elements of the Israelite thanksgiving hymn give expression to the celebration of the character and deeds of Yahweh. In the cult of ancient Israel this poem has probably functioned as liturgy to express God’s power over and against all other powers in creation and in history. In a polemic manner it serves as a remembrance and re-enactment of the incomparable God’s power as the “God of gods” and the “Lord of lords”. The psalm has a unique composition and structure in the Psalter. It also reflects a variety of poetic features that serve as literary vehicles to enhance the psalm’s theological content. For the cultic Sitz im Leben a variety of possibilities exists where Psalm 136 could have functioned. Although it is difficult to exactly date the text, there are indications in the psalm that it could be dated back to the end of the fifth or to the beginning of the fourth century BCE.